Structural homologies between two HLA B27-restricted peptides suggest residues important for interaction with HLA B27. - Huet, S; Nixon, D; Rothbard, J; Townsend, A; Ellis, SA; Mcmichael, A (1990)
Recently we described an HLA B27-restricted peptide derived from HIV gag p24 protein. In this study we have isolated an HLA B27-restricted peptide from the nucleoprotein (NP) of influenza A virus. The shortest fragment recognized by cytotoxic T lymphocyte (CTL) is eight amino acids long, residues 384-391. Comparison of the sequence of these two HLA B27 restricted peptides reveals homologies which can be aligned from one peptide to the other. Of the eight residues, two are identical: tryptophan and isoleucine. Both peptides have a positively charged residue at the N terminus, lysine at position 265 of gag and arginine at position 384 of NP. Using modified peptides we have shown that lysine or arginine is crucial for the interaction with HLA B27. The wild-type gag peptide blocked CTL recognition of NP peptide by influenza-specific CTL, but removal of the lysine prevented inhibition of NP peptide recognition. The importance of these charged residues was confirmed by the observation that truncated NP and gag peptides where the lysine or arginine was removed were not recognized by specific CTL. Further studies showed that the tryptophan residue influenced the association of the gag peptide with HLA B27, because the affinity of the gag peptide for B27 was strongly increased after replacing this residue with a leucine or a tyrosine. However, these peptides were not recognized by gag-specific CTL, suggesting that the tryptophan may interact with both HLA B27 and T cell receptor. These observations should help in the identification of HLA B27-restricted peptides from other viruses or organisms.